Chicken DDX3X Activates IFN-β via the chSTING-chIRF7-IFN-β Signaling Axis - Niu, Qiaona; Cheng, Yuqiang; Wang, Hengan; Yan, Yaxian; Sun, Jianhe (Frontiers in Immunology, 2019)
Asp-Glu-Ala-Asp (DEAD)-box polypeptide 3X (DDX3X) is an ATP-dependent RNA helicase, In addition to involvement of eukaryotic gene expression regulation, mammalian DDX3X has recently been found to regulate IFN-β production via the adaptor MAVS mediated cascade signaling. In our studies, we demonstrated that chicken DDX3X (chDDX3X) is also involved in the IFN-β regulation, and demonstrated that chDDX3X regulated IFN-β via an essential adaptor chicken stimulator of IFN genes (chSTING). We found that chDDX3X overexpression in DF-1 cells induced expression of IFN-β and inhibited avian influenza virus (AIV) or Newcastle disease virus (NDV) replication. Knockdown of chDDX3X decreased the production of IFN-β induced by RNA analog polyinosinic-polycytidylic acid and increased viral yield. Furthermore, chicken chDDX3X was identified as a potential chSTING-interacting protein by endogenous co-immunoprecipitation (Co-IP) and liquid chromatography-tandem mass spectrometry (LC-MS/MS). And exogenous Co-IP in transfected cells with or without virus-stimulations cells further confirmed the interaction between chDDX3X and chSTING. With the gene overexpression and RNA interference studies, the chDDX3X was confirmed to be located upstream of chSTING and activate IFN-β via the chSTING-chTBK1-chIRF7-IFN-β signaling axis. In brief, our results suggest that chDDX3X is an important IFN-β mediator and is involved in RNA- and RNA virus-mediated chDDX3X-chSTING-IFN-β signaling pathway.